Pembuatan Display Produk Unggulan UMK Di Desa Duwet Kecamatan Tumpang - Indrazno Siradjuddin; Sidik Nurcahyo; Lucky Nindya Palupi; Sungkono Sungkono; Herwandi Herwandi (P3M Politeknik Negeri Malang, 2022)
Duwet Village have potential that cannot be underestimated. Duwet Village has a UMK that can produce several superior products, including corn rice (gerit), cassava crackers and bamboo crafts (besek). They need media that can be used for marketing media. However, the lack of promotion of the mainstay products produced by Duwet Village can affect the sustainability Therefore, we need a promotional media for superior products in Duwet village that can improve the quality of as well as support efforts to increase consumers of the mainstay products in Duwet village. Given the beauty of a promotional media but also a very effective promotional media and can bring many benefits to a business. With this problem, we propose the manufacture of displays of superior products from Duwet village. This display will be used as a special place to place corn rice, cassava crackers and bamboo crafts which are the mainstay of Duwet village. This display is very useful as a medium for promoting flagship products to all visitors who come to Duwet village which incidentally will become one of the local tourist destinations in Malang Regency.